The chemical changing during fermentation of cassava tuber skin and its utilization in broiler chicken ration - Supriyati .; I.P Kompiang (Jurnal Ilmu Ternak dan Veteriner, 2002)
Cassava tuber skin is a by-product of cassava chip industry, solid state fermented using mixed inorganic nitrogen and Aspergillus niger. The fermentation process was carried out for 3-4 days. The chemical changing during fermentation of cassava tuber skin and its utilization in broiler chicken ration were studied. After fermentation showed that the crude protein, crude protein digestibility, crude fat, ash, Ca, Ca digestibility, P, and P digestibility improved. The contents of crude protein and its digestibility improved from 4.80% and 66.90% to 28.00% and 72.00%, respectively. The crude fat content improved from 1.32% to 1.80%. The ash content improved from 7.80% to 9.20%, this was followed by improving of Ca and P from 0.97% and 0.11% to 1.69% and 0.68%, respectively. Also the Ca and P digestibilities improved from 81.10% and 14.10% to 93.20% and 52.00%, respectively. The crude fiber content decreased from 21,20% to 14,96 %, cianide acid (HCN) and urea contents also decreased. The result of feeding trial showed that the inclusion of fermented cassava tuber skin up to 10% in chicken broiler ration for 4 weeks feeding showed that the feed consumption, bodyweight gain and FCR were not different significantly (P>0.05). However, 15% inclusion reduced bodyweight gain and increased significantly FCR (P<0.05). It could be concluded that the nutrient content of cassava tuber skin improved after fermentation and the fermentation product could be used up 10% in broiler ration.   Key words: Nutrient composition, cassava tuber skin, fermentation, broiler ration